PROFILE OF RADIOTHERAPY SERVICE USERS FROM A UNIVERSITY HOSPITAL - Michele Carvalho Karkow; Nara Marilene Oliveira Girardon-Perlini; Claudelí Mistura; Bruna Vanessa Costa da Rosa; Natanna da Rosa; Mayani Suertegaray Martins; Paula dos Santos Debus; Vera Cristina Dorneles Santos (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211035 Aim: to know the socio-demographic and clinical profile of patients treated at the University Hospital of radiotherapy Santa Maria. Method: quantitative,restropctive documental and descriptive study, developed with HUSM's radiotherapy unit . We analyzed 278 records/files of patients seen in 2011. Data were collected May-August 2012, through a form and analyzed with descriptive statistics. Results: patients served are predominantly white men, mean age 58 years, married, low education, living in urban area, primarily diagnosed with breast, prostate or lung cancer. Conclusion: the knowledge of the characteristics of the population served can contribute to the improvement of health care.